Zonation of Development Area of Agriculture, Forestry, and Fisheries Sector in West Kutai Regency - Karmini Karmini (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2018)
The effort of development on agriculture, forestry, and fisheries sector in West Kutai Regency needs to be done by integrating the working program that will be formulated for a specific region.  The aim of this study was to know the activities distribution and production of agriculture, forestry, and fisheries products in West Kutai Regency alsothe zone of development area for basis to formulate the efforts to develop agriculture, forestry, and fisheries sector. Studi was done from January to March 2018 in West Kutai Regency, East Kalimantan Province.  Data collected in this study were secondary data from Statistics West Kutai Regency. Data analysis by using descriptive statistics was applied to determine zone of development area.Geografics Information System (GIS) was used to make map of area zonation.Area of West Kutai Regency could be divided into 3zonesbased on wide of agriculture and fisheries areas, they are narrow  area of agriculture and fisheries (Zone I = 5.030,65 – 11.397,71 ha), medium (Zone II = 11.397,72 – 17.764,80 ha), and wide (Zone III = 17.764,81  – 24.131,89 ha).Zone I includes Districts of Bongan, Penyinggahan, Muara Pahu, Muara Lawa, Bentian Besar, Linggang Bigung, Nyuatan, M. Manaar Bulatn, and Tering. Zone II consists Districts of  Barong Tongkok and Long Iram. Zone III is Districts of Jempang, Damai, Melak, Siluq Ngurai, and Sekolaq Darat.